2014
DOI: 10.1105/tpc.114.124628
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisTransporter MGT6 Mediates Magnesium Uptake and Is Required for Growth under Magnesium Limitation

Abstract: Although magnesium (Mg 2+ ) is the most abundant divalent cation in plant cells, little is known about the mechanism of Mg 2+ uptake by plant roots. Here, we report a key function of Magnesium Transport6 (MGT6)/Mitochondrial RNA Splicing2-4 in Mg 2+ uptake and low-Mg 2+ tolerance in Arabidopsis thaliana. MGT6 is expressed mainly in plant aerial tissues when Mg 2+ levels are high in the soil or growth medium. Its expression is highly induced in the roots during Mg 2+ deficiency, suggesting a role for MGT6 in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 40 publications
5
111
0
Order By: Relevance
“…10 Although little change in the expression levels of these MgTRs were observed in microarray analysis when the plants were under MgSs, [8][9][10] results obtained from real time PCR detection showed significant changes for many MgTRs, for example AtMGT6 responding to Mg starvation. 30 We recently found that 8 AtMGTs and AtMHX were responding to MgT 1 and the findings were consistent with results obtained from serpentine conditions, where 6 MgTRs were highly expressed in the mesophyll and some could be correlated with higher accumulation of Mg in plants. 34 These indicate that most of MgTRs are more sensitive to MgT than to MgD.…”
Section: Magnesium Transporters In Plants Responding To Magnesium Strsupporting
confidence: 88%
See 1 more Smart Citation
“…10 Although little change in the expression levels of these MgTRs were observed in microarray analysis when the plants were under MgSs, [8][9][10] results obtained from real time PCR detection showed significant changes for many MgTRs, for example AtMGT6 responding to Mg starvation. 30 We recently found that 8 AtMGTs and AtMHX were responding to MgT 1 and the findings were consistent with results obtained from serpentine conditions, where 6 MgTRs were highly expressed in the mesophyll and some could be correlated with higher accumulation of Mg in plants. 34 These indicate that most of MgTRs are more sensitive to MgT than to MgD.…”
Section: Magnesium Transporters In Plants Responding To Magnesium Strsupporting
confidence: 88%
“…Moreover, the importance of these genes and transporters could be verified from their diverse subcellular localization, for instance, in plasma membrane, endoplasmic reticulum, vacuole, mitochondria, and chloroplast. 27,30 However, only AtMGT6, were discovered in responding to Mg starvation. The dwarf phenotypes of the later 2 mutants under MgD treatments could be ameliorated with lowering Ca 2C concentration, 33 indicating the role of these transporters in Ca 2C and Mg 2C homeostasis in cells.…”
Section: Magnesium Transporters In Plants Responding To Magnesium Strmentioning
confidence: 99%
“…There are 10 MGT homologs in the Arabidopsis genome and nine homologs in rice (Schock et al, 2000;Gebert et al, 2009). Among them, AtMGT6 in Arabidopsis and OsMGT1 in rice mediate root Mg uptake, respectively, although they differ in their gene expression patterns (Mao et al, 2014;Chen et al, 2012). In this study, we found that OsMGT1 is involved in enhancing OsHKT1;5 transport activity at least in rice.…”
mentioning
confidence: 53%
“…Therefore, it is essential for photosynthesis. Recent studies have revealed that several mitochondrial RNA splicing2 (MRS2)/magnesium transport (MGT) proteins, which are structurally homologous to bacterial Co 2+ resistance A (CorA) proteins and ALUMINUM RESISTANCE1 (ALR1), ALR2, and MRS2 in yeast, play an important role in Mg 2+ transport and plant growth under low external Mg 2+ conditions (Gebert et al, 2009;Lenz et al, 2013;Mao et al, 2014). However, it remains largely unknown how plants maintain cellular Mg 2+ homeostasis under high external Mg 2+ conditions.…”
Section: Discussionmentioning
confidence: 99%